Aims of the Childhood Myasthenia Gravis Study Group in Japan. Issue 3 (9th May 2020) - Hayashi, Masatoshi; Nomura, Yoshiko
Abstract: A Japanese epidemiological study about the age of onset of myasthenia gravis (MG) showed the highest peak at ages <5 years, besides the peak observed in adults, which was confirmed in east Asian populations, such as Korea, China and Hong Kong, and is different from that observed in white populations. The Childhood MG Study Group in Japan held an annual workshop for 12 years (from 2006 to 2017), in which the participants debated and obtained information about the clinical problems and related basic sciences of childhood MG. This workshop featured two kinds of presentations: research and clinical experiences. For the case presentation, 42 cases were reported, of which 14 were ocular MG and 28 were generalized MG, including nine cases of latent generalized MG. Seronegative MG was reported in eight cases, muscle‐specific receptor tyrosine kinase‐positive MG in one case and congenital myasthenic syndrome in four cases. Treatment of MG patients was various; tacrolimus was used for 23 cases, cyclosporine for two, a high dose of gamma‐globulin for 13 and thymectomy for 10. For the research presentation, various points of view were reported about the pathogenetic mechanism or treatment by top neurologists and scientists in Japan. This workshop will contribute to continued efforts of clinicians to treat patients, and researchers further progressing in their studies. Abstract : The Childhood Myasthenia Gravis Study Group in Japan held an annual workshop for 12 years (from 2006 to 2017), where the participants debated and obtained information about the clinical problems and related basic sciences of childhood myasthenia gravis. We would like to summarize and introduce the content discussed on this workshop.